EFFECT OF RISK MONITORING ON PERFORMANCE OF FINANCIAL INSTITUTIONS - Kiprop, Lagat Fredrick; Tenai, Dr. Joel (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of the study was to examine the effect of risk monitoring on performance of financial institutions. Methodology: The study used explanatory research design. The study used stratified random sampling to select respondents from target population comprising of managers of 46 commercial banks, 52 Micro Finance institutions (MFIs) and 200 SACCOs and a sample size of 239 respondents obtained. Data was collected using questionnaires. Descriptive statistics was presented, while inferential statistics was done using Pearson product moment correlation. Results: Risk monitoring [r = 0.206, p<.05] had a positive relationship performance of financial institutions. The more there was risk monitoring the higher the performance of financial institutions. A proper risk monitoring practices was used to ensure that risks are in line with financial institution's management goals in order to uncover mistakes at early stages. The risk monitoring had positive relationship on performance of financial institutions (P<0.05). The null hypothesis (HO4) stating that there is no significant effect of risk monitoring on the performance of financial institutions was rejected. The risk evaluation should be enhanced so as to enhance the performance of financial institutions. These may be achieved through establishing regulatory mechanism that can be adopted to enhance effective risk identification. Unique contribution to theory, practice and policy: The risk monitoring should be enhanced so as to enhance the performance of financial institutions. These may be achieved through establishing regulatory mechanism that can be adopted to enhance effective risk identification. Key words: Risk montoring, performance, financial institutions